Hubungan Pengetahuan dan Pekerjaan Ibu dengan Pemberian ASI Ekslusif pada Bayi 7-12 Bulan di Puskesmas Benu-Benua Kota Kendari - Demmalewa, Jenny Qlifianti (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2014)
Breast milk (ASI) is the best food for babies. Breast milk has a unique composition, perfect biochemical composition for babies' needs, and protects babies from the dangers of malnutrition and infectious diseases. Kendari. This research is an observational study with a cross sectional study design and was carried out on 6 - 23 August 2014 in the working area of ​​the Benu-Benua Public Health Center. The population in this study were all mothers who had babies 6-12 months old in the Benu-Benua Health Center working area, Kendari City as many as 108 people. And a sample of 85 people who were taken by purposive random sampling, the data were obtained using a questionnaire and tested using the Chi-test. Square. The thesis is obtained from 85 samples, most of which are 55.3% of mothers' knowledge in the poor category, 51.8% of mothers who do not work (housewives), 68.2% do not give exclusive breastfeeding to their children. Then of the 58 mothers who did not give exclusive breastfeeding, most of them, namely 70.7% of their knowledge in the less category and 58.6% of working mothers. Then of the 27 mothers who gave exclusive breastfeeding, most of them were 77.8% of mothers' knowledge in the sufficient category and 74.1% of mothers who did not work. The conclusion in this study is that there is a relationship between the level of knowledge and the mother's employment status with exclusive breastfeeding for infants 0-6 months at the Benu-Benua Health Center, Kendari City. Suggestions in this study are for nutritionists at the Benu-Benua Health Center, they should provide counseling to infant mothers about the importance of nutrients contained in breast milk. for children under five, thereby increasing mother's knowledge, especially in choosing nutritious food for her baby. For mothers to always provide nutritious food according to the needs of their children and for the community, they should follow the development of health information, especially regarding children under five through counseling activities as well as from print and electronic media.